Corporate Championing and Antagonism as Forms of Political Behavior: An R&D Perspective - Markham, Stephen K. (Organization Science, 2000)
Individuals in general management, marketing, production, and customer service undertake corporate political roles of championing and antagonism in support of or opposition to research and development (R&D) projects. R&D personnel see these champions acting politically because they favor projects that align more closely with the firm's business interests than with its specific technologies. Champions find resources and protect their projects from termination; however, they are equally likely to support high and low performing projects. These results contradict many of the commonly held beliefs in research literature about champions. Antagonists, in a role of friendly opposition, appear to react to the presence of champions and do not appear to affect resources or project termination.